1992
DOI: 10.1128/aem.58.2.731-733.1992
|View full text |Cite
|
Sign up to set email alerts
|

Production of an extracellular polyethylene-degrading enzyme(s) by Streptomyces species

Abstract: Extracellular culture concentrates were prepared from Streptomyces viridosporus T7A, Streptomyces badius 252, and Streptomyces setonii 75Vi2 shake flask cultures. Ten-day-heat-treated (70°C) starch-polyethylene degradable plastic films were incubated with shaking with active or inactive enzyme for 3 weeks (37C). Active enzyme illustrated changes in the films' Fourier transform infrared spectra, mechanical properties, and polyethylene molecular weight distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(29 citation statements)
references
References 6 publications
0
28
0
1
Order By: Relevance
“…However, some works5–7 have demonstrated that ligninolytic and cellulolytic fungi ( Phanerochaete chrysosporium , Aspergillus niger , Penicillium pinophilum , Gliocadium virens , Paecilomyces variotti ) can degrade oxidized PE products. Pometto et al8 found an extracellular enzyme in a Streptomyces sp. extract, able to attack and modify thermo‐oxidized PE‐starch films (70°C, 10 days) after three weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, some works5–7 have demonstrated that ligninolytic and cellulolytic fungi ( Phanerochaete chrysosporium , Aspergillus niger , Penicillium pinophilum , Gliocadium virens , Paecilomyces variotti ) can degrade oxidized PE products. Pometto et al8 found an extracellular enzyme in a Streptomyces sp. extract, able to attack and modify thermo‐oxidized PE‐starch films (70°C, 10 days) after three weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Since this is not the case, the root cause for the differential and quick degradation of OPENac can only be attributed to the different biotic environment created by nanoclay. The results of some articles published in the literature on biodegradation of thermo‐oxidised OPE in soil and composting units also support this theory 32–34…”
Section: Resultsmentioning
confidence: 63%
“…have been utilized during the degradation of polyethylene for their effective biodegradation ability. [11][12][13][14] In a study by Nowak et al, Pseudomonas fluorescens was isolated from polyethylene surface. 15 It has also been found that P. fluorescens is able to form biofilm on the un-oxidized polyethylene surface during initial biodegradation process.…”
Section: Introductionmentioning
confidence: 99%